Corrosion resistance of reinforced layers of 15Х11MF steel steam turbine blades - Hlushkova, D.B.; Bahrov, V.A.; Hrinchenko, O.D.; Hnatiuk, A.A.; Kalinina, N.E.; Kalinin, V.T. (Вопросы атомной науки и техники, 2021)
The reliability of the vane apparatus of steam turbines largely determines the operation of the turbine as a whole. The results of scientific research indicate that the surface operation of the blades in the wet-steam flow is caused by a combination of corrosion and drip erosion. The presence of chemical elements and compounds in the working fluid intensifies the process of blade wear. The pH value of the working environment, which can fluctuate significantly during operation, has a significant effect on the wear characteristics. The influence of methods of strengthening the leading edges of steam turbine blades made of steel is analyzed 15H11MF on corrosion resistance. Corrosion tests of blade samples were carried out, the inlet edges of which were strengthened in three ways: high current amplification, electrospark alloying with T15K6 alloy, electrospark alloying with steel 15H11MF. According to the results of the tests, the layer strengthened by hardening by high-frequency currents has the lowest corrosion rate, the layer strengthened by electrospark alloying with T15K6 hard alloy has the highest. The corrosion rate of the layer reinforced by electrospark alloying of steel 15H11MF is 2.1 less than that of the layer reinforced with T15K6 alloy. Надійність роботи лопаткового апарата парових турбін у значній мірі визначає роботу турбіни в цілому. Результати наукових досліджень свідчать про те, що поверхневе спрацювання робочих лопаток у вологопаровому потоці викликається поєднанням корозії і каплеударної ерозії. Наявність у робочому тілі хімічних елементів і сполук інтенсифікують процес зносу лопаток. Відчутний вплив на характеристики зносу надає значення рН робочого середовища, яке може значно коливатися в процесі експлуатації. Проаналізовано вплив способів зміцнення вхідних крайок лопаток парових турбін зі сталі 15Х11МФ на корозійну стійкість. Проведено корозійні випробування зразків лопаток, вхідні крайки яких зміцнені трьома способами: струмами високої частоти, електроіскровим легуванням сплавом Т15К6, електроіскровим легуванням сталлю 15Х11МФ. За результатами проведених випробувань найменшу швидкість корозії має шар, зміцнений загартуванням струмами високої частоти, найбільшу - шар, зміцнений електроіскровим легуванням твердим сплавом Т15К6. Швидкість корозії шару, зміцненого електроіскровим легуванням сталлю 15Х11МФ, у 2,1 рази менше, ніж у шару, зміцненого сплавом Т15К6. Надежность работы лопаточного аппарата паровых турбин в значительной степени определяет работу турбины в целом. Результаты научных исследований свидетельствуют о том, что поверхностный износ рабочих лопаток во влажно-паровом потоке вызывается сочетанием коррозии и каплеударной эрозии. Наличие в рабочем теле химических элементов и соединений интенсифицируют процесс износа лопаток. Ощутимое влияние на характеристики износа имеет значение рН рабочей среды, которое может значительно колебаться в процессе эксплуатации. Проанализировано влияние способов упрочнения входных кромок лопаток паровых турбин из стали 15Х11МФ на коррозионную стойкость. Проведены коррозионные испытания образцов лопаток, входные кромки которых упрочнены тремя способами: токами высокой частоты, электроискровым легированием сплавом Т15К6, электроискровым легированием сталью 15Х11МФ-Ш. По результатам проведенных испытаний наименьшую скорость коррозии имеет слой, упрочненный закалкой токами высокой частоты, наибольшую - слой, упрочненный электроискровым легированием твердым сплавом Т15К6. Скорость коррозии слоя, упрочненного электроискровым легированием сталью 15Х11МФ, в 2,1 раза меньше, чем у слоя, укрепленного сплавом Т15К6.